PENGEMBANGAN MODUL BERBASIS KONTEKSTUAL PADA MATERI BARISAN DAN DERET - Khairun Nisa; Ade Susanti; Sugeng Riyadi (Pendidikan Matematika | STKIP YM Bangko, 2021)
In the learning process carried out in class the teacher has not yet developed teaching material. One of the teaching materials that can help students in the learning process is a module. A good module is one that can link the material to the daily lives of students, so in the contextual context-based module will be developed on the rank and sequence material of class XI students of SMA Negeri 17 Merangin 2019/2020 school year. This type of research is research and development. This study uses a 4-D model which consists of 4 stages: the defining stage, the design phase, the development stage and the disseminate stage. The contextual based module is validated by five experts namely three material experts, one Indonesian language expert and one media expert. Validity is seen from the results of the validation sheet, while practicality is seen from the questionnaire practicality of students' responses. The results of the analysis at the validation stage showed that the average score of the results of validation by material experts was 4.22, validation by linguists was 4.00 and validation was by media experts 4.94, so overall of each validation obtained an average of 4.38 with very valid category. The results of the questionnaire practicality analysis show that the practicality of contextual-based modules is produced practically with a percentage of 84.75%. Based on the results of the study it was found that the module developed was valid and practical.